2019
DOI: 10.12765/cpos-2019-19
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Dementia and Extremity Injuries on the Plasticity of Long-term Care Demand: An Analysis of Counterfactual Projection Scenarios Based on German Health Insurance Routine Data

Abstract: Although demand for long-term care (LTC) in Germany is expected to increase over the coming decades, the LTC sector will struggle to provide sufficient capacity. Evaluating the impact of different risk factors on future LTC demand is necessary in order to make informed policy decisions. With regard to LTC need, dementia and lower extremity injuries (LEI) are common risk factors. Both are used to demonstrate their maximum attainable efficacy in mitigating the future increase in overall LTC need, both at home an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
2
0
0
Order By: Relevance
“…Most of the social pension services are currently paid services, which means that economic level is a limiting factor for the elderly who choose the social pension. Many studies [38,39] have shown that the elderly with higher economic status are more likely to choose the social pension because of their strong ability to pay for pension services, and this is further confirmed by this study.…”
Section: Factors Influencing Preference For Cmcp Servicesupporting
confidence: 86%
“…Most of the social pension services are currently paid services, which means that economic level is a limiting factor for the elderly who choose the social pension. Many studies [38,39] have shown that the elderly with higher economic status are more likely to choose the social pension because of their strong ability to pay for pension services, and this is further confirmed by this study.…”
Section: Factors Influencing Preference For Cmcp Servicesupporting
confidence: 86%
“…Additionally, Economic status and medical insurance were important factors. Most studies indicated that low-income older people chose home care, which was consistent with previous studies (Barth, 2019;Edwards & Sen, 2019). While the rate of institutional care for older people, who were covered by medical or endowment insurance, has risen sharply.…”
Section: Discussionsupporting
confidence: 88%